Molecular characterization of Potato virus Y (PVY) and Potato virus V (PVV) isolates naturally infecting cape gooseberry (Physalis peruviana) in Antioquia, Colombia - Natalia Álvarez Mesa (Agronomía Colombiana, 2018)
Due to the increase of the international demand for functional fruits, cape gooseberry (Physalis peruviana) has become one of the crops of highest expansion in Colombia and the Andean region of South America. nfortunately, the emergence of fungal and unidentified viral diseases has slowed down the cultivation of cape gooseberry in Colombia and, particularly, in the department of Antioquia. In this work, a next-generation sequencing virome analysis of cape gooseberry plants from eastern Antioquia was performed, using leaves exhibiting symptoms such as mosaics, leaf deformation and greening of veins. The complete genomes of Potato virus Y (PVY) and Potato virus V (PVV) were obtained in the assembled data. The presence of both viruses was confirmed in the samples obtained at two commercial cape gooseberry fields by real time RT-PCR (RT-qPCR) and partial Sanger sequencing of the coat protein (CP). Sequence analysis revealed significant sequence similarity between PVY and PVV isolates infecting P. peruviana to previously identified strains infecting potato (Solanum tuberosum and S. phureja) and tomato (Solanum lycopersicum) in the same geographical region. This study suggests that cape gooseberry could be an alternate host to viruses of other economically important solanaceous crops in the Andean region of South America.